1982
DOI: 10.3109/00016348209156959
|View full text |Cite
|
Sign up to set email alerts
|

Constriction of the Umbilical Cord by an Amniotic Band After Midtrimester Amniocentesis

Abstract: Constriction of the umbilical cord by an amniotic band after previous midtrimester amniocentesis is an extremely rare entity. A case report of fetal asphyxia caused by partial occlusion of the umbilical cord by an amniotic band is presented. Clinical and experimental evidence strongly suggests that the pathogenesis of this defect is related to early rupture of the membranes during gestation with subsequent encirclement and ligation of fetal umbilical cord, or extremities. In this case, formation of the amnioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Of these 15 term deliveries, there were three reported emergency cesarean sections due to fetal distress [6,11]. Another baby was born with mild asphyxia associated with an amniotic band around the cord [17].…”
Section: Resultsmentioning
confidence: 99%
“…Of these 15 term deliveries, there were three reported emergency cesarean sections due to fetal distress [6,11]. Another baby was born with mild asphyxia associated with an amniotic band around the cord [17].…”
Section: Resultsmentioning
confidence: 99%
“…2 However, in cases of severe separation, it can lead to amniotic band syndrome. Ashkenazi et al 4 presented a case of encirclement and ligation of the fetal umbilical cord secondary to amniotic band formation. Graf et al 5 described umbilical cord blood flow impairment caused by amniotic bands after fetal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2-7 Separation of the amnion from the chorion after amniocentesis has been reported previously. [2][3][4] We present a case of extensive hemorrhagic chorion-amnion separation (CAS) at 19 weeks' gestation, 2 days after amniocentesis. It was complicated by preterm premature rupture of membranes at 23 weeks and preterm delivery at 31 weeks.…”
mentioning
confidence: 99%
“…There have been isolated case reports of constriction band syndrome occurring following intrauterine instrumentation, such as amniocentesis (11)(12)(13)(14)(15), chorionic villus sampling (16) or the placement of an intrauterine contraceptive device (10). No clear causative link has been established, but it is suggested that the instrumentation required in the IVF procedure may have played a role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there have been reports associating amniotic band syndrome with maternal trauma, oophorectomy during pregnancy (9), intrauterine contraceptive device (10), amniocentesis (11)(12)(13)(14)(15) and chorionic villus sampling (16).…”
mentioning
confidence: 99%